Dmytro Olexandrovych Yaremenko - Ukrainian association of orthopaedists-traumatologists, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article deals with the 75th birthday of D.O. Yaremenko – Doctor of Medical Science, Professor, a leading orthopaedist-traumatologist and organizer of health service, and a talented scientist, whose name is well known in Ukraine and beyond its borders.